Antes de o que, há sempre um porquê: motivações para comer de indivíduos adultos - Bazzan, Luma Stella Teichmann (2022)
Considering the consequences of excessive food consumption of ultra-processed foods, such as the acceleration of obesity and its consequences, it is important to know not only what people eat, but also why, in order to further assist in intervention proposals for coping of the disease. The study aimed to identify the motivations for food choices of adult individuals and possible associations with sociodemographic data and nutritional status. This was a cross-sectional study carried out in two municipalities in the south of Brazil, with participants between 20 and 59 years old. The questionnaire used included sociodemographic questions (age, sex, marital status, education, income), self-reported weight and height, in addition to the instrument to assess motivations divided into 15 subscales, The Eating Motivation Survey (TEMS). A total of 371 individuals participated, in which middle-aged adults ate for preference (p=0.026) and health (p =0.001) and the younger ones for visual attraction (p=0.019). Males (p=0.002) and those with higher incomes (p=0.008) presented traditional eating as their main motivation, and those who had partners for convenience (p=0.042). Those with less education chose food based on social norms (p=0.04), preference (p=0.02) and price (p=0.039). Finally, overweight individuals were not motivated to eat for reasons of need or hunger (p=0.001), health (p=0.02) or natural reasons (p=0.001). It is concluded that there should be a closer look at younger individuals and people with less education, as the reasons indicated (visual attraction and price) are associated with the consumption of more processed foods, in addition to overweight individuals, as it is understood that precisely the reasons they ignore (health, hunger and naturalness of food) are correlated with health approaches evidenced to promote healthier eating behavior for all individuals.